2018
DOI: 10.1080/09500340.2018.1454527
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of nonclassical properties of multiphoton coherent states from optical tomograms

Abstract: We have examined both single and entangled two-mode multiphoton coherent states and shown how the 'Janus-faced' properties between two partner states are mirrored in appropriate tomograms. Entropic squeezing, quadrature squeezing and higher-order squeezing properties for a wide range of nonclassical states are estimated directly from tomograms. We have demonstrated how squeezing properties of twomode entangled states produced at the output port of a quantum beamsplitter are sensitive to the relative phase betw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…q-deformed odd cat state and qdeformed squeezed excited state. We note that this Janus-faced property of quantum states in optical tomograms is reported for the non-deformed scenarios [23].…”
Section: Janus-faced Tomogramssupporting
confidence: 66%
“…q-deformed odd cat state and qdeformed squeezed excited state. We note that this Janus-faced property of quantum states in optical tomograms is reported for the non-deformed scenarios [23].…”
Section: Janus-faced Tomogramssupporting
confidence: 66%
“…It has been shown that it is possible, solely from tomograms, to assess qualitatively whether subsystems are entangled [6]. The squeezing properties of the state and the entanglement between subsystems [7] have been quantified. Further, specific nonclassical effects have been assessed from tomograms during temporal evolution of single-mode and bipartite systems.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, qualitative signatures of revivals (when a system returns to its initial state apart from an overall phase) and fractional revivals (when the state of a system is a superposition of 'copies' of its initial state) have been identified in tomograms in the case of a single-mode radiation field propagating in a Kerr medium [8]. Decoherence of entangled bipartite states has also been investigated using tomograms [7]. Quadrature and higher-order squeezing of a radiation field subject to cubic nonlinearities have been quantified, and an entanglement indicator which can be inferred from the tomogram for bipartite systems such as a double-well Bose-Einstein condensate(BEC) has been proposed [9].…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of this approach is borne out by several investigations in recent years involving optical tomography. These include: the identification of squeezed light and other nonclassical states of light [30,31]; obtaining qualitative signatures of revivals and fractional revivals of the initial state of a system with a nonlinear Hamiltonian [32,33]; and determining whether a bipartite state is entangled at the output port of a quantum beamsplitter for a specific choice of input states [34,35], directly from the relevant tomogram. We examine both the quadrature and tomographic entropic squeezing properties of the field states and report results on the crucial role played by various forms of IDC on the degree of squeezing.…”
Section: Introductionmentioning
confidence: 99%